2006
DOI: 10.1111/j.1471-4159.2005.03630.x
|View full text |Cite
|
Sign up to set email alerts
|

Septal networks: relevance to theta rhythm, epilepsy and Alzheimer's disease

Abstract: Information processing and storing by brain networks requires a highly coordinated operation of multiple neuronal groups. The function of septal neurons is to modulate the activity of archicortical (e.g. hippocampal) and neocortical circuits. This modulation is necessary for the development and normal occurrence of rhythmical cortical activities that control the processing of sensory information and memory functions.Damage or degeneration of septal neurons results in abnormal information processing in cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 115 publications
(258 reference statements)
6
117
0
2
Order By: Relevance
“…An alternative explanation has to consider the CV damage localization, that could be essential for the changes in EEG rhythmicity. CV lesions in the thalamocortical pathway could affect preferentially the oscillatory activity of the a frequency peak (Steriade and Llinas, 1988;Llinas et al, 1999;Jellinger, 2002Jellinger, , 2005, whereas lesions in cortico-basal or cortico-septal pathways could affect preferentially the oscillatory activity of the transition frequency between a and h frequency bands (Colom, 2006). Obviously, given the correlative nature of this study, these conclusions have to be considered with caution.…”
Section: Eeg Frequency Indices Of a Rhythms And CV Damagementioning
confidence: 79%
See 1 more Smart Citation
“…An alternative explanation has to consider the CV damage localization, that could be essential for the changes in EEG rhythmicity. CV lesions in the thalamocortical pathway could affect preferentially the oscillatory activity of the a frequency peak (Steriade and Llinas, 1988;Llinas et al, 1999;Jellinger, 2002Jellinger, , 2005, whereas lesions in cortico-basal or cortico-septal pathways could affect preferentially the oscillatory activity of the transition frequency between a and h frequency bands (Colom, 2006). Obviously, given the correlative nature of this study, these conclusions have to be considered with caution.…”
Section: Eeg Frequency Indices Of a Rhythms And CV Damagementioning
confidence: 79%
“…Therefore, a h band power increase significantly based on the CV damage could occur when the axonal destructuration reaches a well-defined stage during the course of the disease. Alternatively, a pathological increase of the h band power could be due to a specific vascular impairment of the anatomical network ascending from the brainstem towards the medial septum-hippocampal formation involved in the generation of the h rhythm (Colom, 2006).…”
Section: Relative Power Spectral Density and CV Damagementioning
confidence: 99%
“…A smaller monosynaptic excitatory input to the ipsilateral hippocampal formation projects from the septal region through fornix/fimbria (Crutcher et al, 1981;Swanson and Cowan, 1979). The cell bodies of this largely cholinergic septohippocampal pathway reside in the medial septum with contributions from both the vertical and horizontal limbs of the diagonal band of Broca (Amaral and Kurz, 1985); the bulk of lateral septal efferents projects to medial septal nuclei with little or no input to the hippocampal formation (Colom, 2006). These cells project to the supra-and infragranular layers of the dentate gyrus (Chandler and Crutcher, 1983) and the hippocampus (Amaral and Kurz, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This diversity in firing properties among basal forebrain cholinergic neurons may be related to connectivity. In this case, neurochemically identified medial septal cholinergic neurons may be more electrophysiologically diverse than formerly proposed due to specific connectivity patterns present in each medial septal subregion (Colom, 2006).Our initial analysis of current-clamp recordings from MS/DB neurons revealed that the firing properties of medial septal neurons exhibited great variability. Heterogeneity of firing characteristics was evident in all of the classically-described electrophysiological phenotypes including regular firing, fast spiking and burst-firing neurons.…”
mentioning
confidence: 99%